Grid search based hyperparameter optimization for machine learning based Non-Intrusive load monitoring - CEYLAN, OĞUZHAN (My University, 2023)
This paper solves the Non-Intrusive Load Monitoring problem by using two machine learning based models: Xgboost and Recurrent Neural Network. We utilize and develop models using a publicly available dataset. To improve the performance we have implemented hyperparameter optimization using grid search. The numerical simulation results show that proposed Xgboost model outperforms the RNN based model. With the implementation of hyperparameter optimization an improved numerical accuracy is obtained.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Sinyal İşleme; Bilgisayar Bilimleri; Algoritmalar; Matematik; Temel Bilimler; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Information Systems, Communication and Control Engineering; Signal Processing; Computer Sciences; algorithms; Mathematics; Computer Science; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Bilgisayar Bilimi; Mühendislik; BİLGİSAYAR BİLİMİ, YAPAY ZEKA; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; ENERJİ VE YAKITLAR; MATEMATİK, UYGULAMALI; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); COMPUTER SCIENCE; ENGINEERING; MATHEMATICS; COMPUTER SCIENCE, ARTIFICIAL INTELLIGENCE; ENGINEERING, ELECTRICAL & ELECTRONIC; ENERGY & FUELS; MATHEMATICS, APPLIED; Yapay Zeka; Fizik Bilimleri; Enerji Mühendisliği ve Güç Teknolojisi; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Elektrik ve Elektronik Mühendisliği; Modelleme ve Simülasyon; Artificial Intelligence; Physical Sciences; Energy Engineering and Power Technology; Renewable Energy, Sustainability and the Environment; Electrical and Electronic Engineering; Modeling and Simulation; grid search; hyperparameter optimization; Non-intrusive load monitoring; xgboost